Homoeopathic Arnica and Rhus toxicodendron for delayed onset muscle soreness - Jawara, N.; Lewith, G.T.; Vickers, A.J.; Mullee, M.A.; Smith, C. (British Homeopathic Journal, 1997)
We intend to develop a simple, reproducible, clinical model to test the null hypothesis thatthe effects of ultramolecular homoeopathic preparations are always equivalent to placebo. A pilot of a randomized, double-blind, placebo-controlled study was conducted to assess the effects of Arnica and Rhus tox 30c on delayed onset muscle soreness. 50 healthy volunteers undertook a standard bench-stepping exercise, with outcome assessed using a validated soreness scale. Though the results of the trial favoured homoeopathy, differences between groups were small and did not reach statistical signficance (p>0.2). A sub-group analysis of subjects who did not take vigorous exercise and who would therefore be expected to be more responsive to treatment showed clinically but not statistically significant differences between groups (p>0.2). A second trial is currently under way in an attempt to replicate these findings.